Utilization of Content Based Image Retrieval with Histogram. Equalization (He) for Linking Heart Disease. Using Palm Images - Diqie Shodiq Permono (Proceeding International Conference on Information Technology and Business, 2018)
In CBIR based on images that are seen not the similarity of the image, but the similarity of the distribution of images in the compared image. In general, CBIR based on Histogram is known as Equivalent Histogram method. calculations using the Equivalent Histogram difference can set the order of the highest level of image similarity.In Indonesia, the number of experts in the field of medicine that uses palm diagnosis skills is still very little, this expertise is usually controlled by doctors of traditional and natural medicine. Therefore this writing makes it possible for Doctors in Hospitals or other Medical Centers and Clinics to be able to master it and the program by being trained in advance on how to use it. Because of that the writer took the title